METHOD OF RECOVERING METAL FROM IRONMAKING SLAG - MAEDA KENTARO (2018)
PROBLEM TO BE SOLVED: To provide a method of recovering a metal from an ironmaking slag easily and efficiently.SOLUTION: The method of recovering the metal from the ironmaking slag according to the present invention includes: an advance preparation step in which a supply condition of water to the ironmaking slag and a sieve condition are determined; and a selection step in which water is supplied to the ironmaking slag according to the supply condition determined in the advance preparation step, and the water containing ironmaking slag is sieved according to the sieve condition determined in the advance preparation step. The advance preparation step comprises: a step of measuring the particle size distribution and the composition of the ironmaking slag; a step of investigating the relationship between water content, volume expansion coefficient, and the sieving operation condition of the ironmaking slag; a step of supplying water to the ironmaking slag so as to have the water content determined on the basis of the aforementioned relationship followed by sieving under the sieving operation condition determined similarly; a step of measuring the slag adhering amount of ironmaking slag remaining on the sieve after the aforementioned step; and a step of determining the supply condition of water to the ironmaking slag and the sieve condition of the ironmaking slag on the basis of the measurement result.SELECTED DRAWING: Figure 1 【課題】本発明は、製鉄スラグから効率よく地金を容易に回収する地金回収方法の提供を目的とする。【解決手段】本発明は、製鉄スラグへの水の供給条件及び篩条件を決定する事前準備工程と、事前準備工程によって決定された供給条件で水を製鉄スラグに供給し、含水した製鉄スラグを事前準備工程によって決定された篩条件で篩分けを行う選別工程とを有する。事前準備工程では、製鉄スラグの粒度分布及び成分組成を測定する工程と、製鉄スラグの含水量、体積膨張率、及び篩作業条件の関係を調査する工程と、この関係に基づいて決定した含水量となるよう製鉄スラグに水を供給し篩作業条件で篩分けを行う工程と、この工程後に篩上に残存した製鉄スラグのスラグ付着量を測定する工程と、この測定結果に基づいて製鉄スラグへの水の供給条件及び製鉄スラグの篩条件を決定する工程とを有する。【選択図】図１